ANALYSIS OF BEACH POTENTIAL FOR DEVELOPMENT ECOTOURISM OF BAHARI ISLANDS OF HEBREWS SERDANG BEDAGAI PROVINCE OF NORTH SUMATERA - Siringo-ringo, Irpan suriadi; Yoswaty, Dessy; Thamrin, Thamrin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The study was conducted in June 2019 on Berhala Island, Serdang Bedagai Regency, North Sumatra Province. The research aims to determine the potential of ecotourism in Berhala Island and to analyze the suitability of ecology to be developed as an ecotourism location. The method used is a survey method and the determination of station points by purposive sampling. The results showed that the main marine ecotourism objects of Berhala Island are the beauty of the island, the view of the beach with clear waters, white sand and clean, underwater beauty, and protected animals such as turtles and dolphins and the phenomenon of the sun rising from above the lighthouse. The value of the Tourism Suitability Index ranges from 85.26 to 94.23%.Strategy (WO) Increasing the promotion of tourism on a national and international scale, construction of tourist support facilities, improving the quality of human resources through education and training. Strategy (SO) Development of marine tourism with the concept of ecotourism, creating jobs and preserving nature and maintaining the sovereignty of the State. Strategy (ST) Preparation of detailed zoning and regulations for the development of marine ecotourism potential, environmental utilization does not exceed the carrying capacity of the region, forming a special team for supervision of marine ecotourism potential development activities. Strategy (WT) Counseling about the importance of environmental conservation, pollution hazards, and natural disaster management, developing accessibility to the island. Keywords:Potential, Marine Ecotourism, SWOT Analysis, Berhala Island